Pengadaan Barang di Gudang PT. Bumitama Gunajaya Agro Kecamatan Kota Waringin Barat Barat Kalimantan Tengah - Zein, Kevin; Ambarsari, Arum; Manumono, Danang (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
This research aims to determine the procedures for procurement of goods in warehouses related to company operations. This research uses a basic qualitative descriptive method, a location determination method using a purposive method and was carried out at PT. Bumitama Gunajaya Agro (BGA). Data obtained from interviews with the Head of Warehouse, Warehouse Mador and KTU. The results obtained from this research are that the procurement of goods in warehouses has been implemented by PT. Bumitama Gunajaya Agro has used procurement procedures from planning to control, but there is still a need for coordination between the estate warehouse and the central warehouse.